Interlocked feedback loops contribute to the robustness of the Neurospora circadian clock - Cheng, Ping (The National Academy of Sciences, 2001)
Interlocked feedback loops may represent a common feature among the regulatory systems controlling circadian rhythms. The Neurospora circadian feedback loops involve white collar-1 (wc-1), wc-2, and frequency (frq) genes. We show that WC-1 and WC-2 proteins activate the transcription of frq gene, whereas FRQ protein plays dual roles: repressing its own transcription, probably by interacting with the WC-1/WC-2 complex, and activating the expression of both WC proteins. Thus, they form two interlocked feedback loops: one negative and one positive. We establish the physiological significance of the interlocked positive feedback loops by showing that the levels of WC-1 and WC-2 determine the robustness and stability of the clock. Our data demonstrate that with WC-1 being the limiting factor in the WC-1/WC-2 complex, the greater the levels of WC-1 and WC-2, the higher the level of the FRQ oscillation and the more robust the overt rhythms. Our data also show that, despite considerable changes in the levels of WC-1, WC-2, and FRQ, the period of the clock has been limited to a small range, suggesting that the interlocked circadian feedback loops are also important for determining the circadian period length of the clock.